Response to Temozolomide in patients with metastatic melanoma in a third level medical facility: Respuesta a Temozolomida en pacientes con melanoma metastásico en un hospital de tercer nivel de atención - Mejía-Cabrera, Selene (2022)
Introduction.Melanoma is a public health problem; it represents 4% of malignant skin tumors and is responsible for 80% of deaths from this type of neoplasm. Objective: Show the response to Temozolomide in patients with metastatic melanoma. Methods: Descriptive, cross-sectional study. The clinical response of patients with metastatic melanoma, managed with Temozolomide 200 mg/m2 once a day was analyzed for 5 days every 28 days. The risk factors analyzed were: histological variety, topographic region of the primary lesion, metastasis, ulceration, and Breslow. Descriptive statistics were used for normality Kolmogorov-Smirnoff, Student's t-test, and binary logistic regression. Results: There were 51 les, 47 met the criteria; 25 men, 22 women, mean age 54.45, minimum 22, maximum 85 years, Complete response was obtained in 3 (6.3%), partial response in 7 (14.8%), stable disease in 10 (21%) and disease progression in 27 (57.44%) patients. The presence of ulceration is associated with a higher Breslow index and, as a result, a higher risk of disease progression. Conclusions: Temozolomide as monotherapy is a treatment that presents low rates of complete response and partial response, showing better results in patients with lymph node metastases.